Cardiovascular autonomic dysfunction, altered sleep architecture, and muscle overactivity during nocturnal sleep in pediatric patients with narcolepsy type 1. Issue 12 (29th July 2019) - Vandi, Stefano; Rodolfi, Sara; Pizza, Fabio; Moresco, Monica; Antelmi, Elena; Ferri, Raffaele; Mignot, Emmanuel; Plazzi, Giuseppe; Silvani, Alessandro
Abstract: Study Objectives: Arterial blood pressure (ABP) decreases during sleep compared with wakefulness and this change is blunted in mouse models of and adult patients with narcolepsy type 1 (NT1). We tested whether: (1) pediatric patients with NT1 have similar cardiovascular autonomic abnormalities during nocturnal sleep; and (2) these abnormalities can be linked to hypocretin-1 cerebrospinal fluid concentration (CSF HCRT-1), sleep architecture, or muscle activity. Methods: Laboratory polysomnographic studies were performed in 27 consecutive drug-naïve NT1 children or adolescents and in 19 matched controls. Nocturnal sleep architecture and submentalis (SM), tibialis anterior (TA), and hand extensor (HE) electromyographic (EMG) activity were analyzed. Cardiovascular autonomic function was assessed through the analysis of pulse transit time (PTT) and heart period (HP). Results: PTT showed reduced lengthening during total sleep and REM sleep compared with nocturnal wakefulness in NT1 patients than in controls, whereas HP did not. NT1 patients had altered sleep architecture, higher SM EMG during REM sleep, and higher TA and HE EMG during N1–N3 and REM sleep when compared with controls. PTT alterations found in NT1 patients were more severe in subjects with lower CSF HRCT-1, but did not cluster or correlate with sleep architecture alterations or muscle overactivity during sleep. Conclusion: Our results suggest that pediatric NT1 patients close to disease onset have impaired capability to modulate ABP as a function of nocturnal wake–sleep transitions, possibly as a direct consequence of hypocretin neuron loss. The relevance of this finding for cardiovascular risk later in life remains to be determined.